Multiplayer Pursuit-Evasion Differential Games With Malicious Pursuers - Xu, Yuhang; Yang, Hao; Jiang, Bin; Polycarpou, Marios M. (IEEE transactions on automatic control, 2022)
This article investigates the multiplayer pursuit-evasion (MPE) differential games in the presence of malicious pursuers. First, three types of malicious pursuers, namely greedy , lazy , and traitorous pursuers are formulated by using two subjectively malicious factors in the performance index. Then, an N -player nonzero-sum game framework is established to study the relationships among healthy pursuers, malicious pursuers, and evaders. The capturability and Nash equilibrium of such a new MPE differential game are rigorously analyzed. Finally, the effects of malicious pursuers on the capture time are explicitly quantified by the minimal pursuit coefficient , whose explicit form is obtained by the solutions from coupled Riccati differential equations.